Sub-Antarctic Flux and Dynamics Experiment Inverted Echo Sounder Data Report for March 1995 to March 1997 - Tracey, Karen L.; Watts, D. Randolph (DigitalCommons@URI, 2016)
This report focuses on the inverted echo sounder (IES) data collected as part of the Sub-Antarctic Flux and Dynamics Experiment (SAFDE) during March 1995 -- March 1997. The collection, processing and calibration of the IES data are described. The measurements were made under the support of the National Science Foundation.